2014
DOI: 10.2166/aqua.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of consumer preferences on the drinking water market: today to the future

Abstract: In the 21st century, water has become a priority issue as a vital commodity which has no substitute and has growing economic and strategic value. It is predicted that a significant part of the world population will be faced with drinking water problems in the coming years. This study was focused on the determination of consumer preference trends for drinking water. In the scope of the study, the primary data used were obtained from 965 households in Turkey. According to the study, 28.6% of households surveyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The analysis tools used and the parameters analyzed are different. They mainly used questionnaires and surveys (Akpinar & Gul, 2014;Adams & Zulu 2015;Dziedzic & Karney, 2016). These studies have led to two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis tools used and the parameters analyzed are different. They mainly used questionnaires and surveys (Akpinar & Gul, 2014;Adams & Zulu 2015;Dziedzic & Karney, 2016). These studies have led to two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Gul (2014) found that lower income would predict the absence of bottle use in Turkey. Still other studies(Abrahams et al 2000;O'Donnell & Rice 2012) found that non-white populations were more likely to use bottled water in the US.…”
mentioning
confidence: 99%
“…
Nowadays people often prefer to buy bottled water instead of drinking the tap water. Stores are full of different bottled waters and studies have demonstrated that people tend to consider the bottled water to have high quality (Ward et al 2009, Akpinar et al 2014. The aim of this research was to find out the compliance of bottled water sold in Estonia with the established microbiological normatives.
…”
mentioning
confidence: 99%